Gated communities?: Regulating migration in early modern cities - Munck, Bert de; Winter, Anne (Ashgate, 2012)
Regulating migration in early modern cities : an introduction / Bert De Munck and Anne Winter -- Repertoires of inclusion and exclusion : guilds and citizenship -- Migrant workers and illicit labour : regulating the immigration of building workers in sixteenth-century Antwerp / Jan De Meester -- Craft guilds and immigration : Huguenots in German and English cities / Ulrich Niggemann -- Heresy, war, vagrancy, and labour needs : dealing with temporary migrants in the textile towns of Flanders, Artois and Hainaut in the wake of the Dutch revolt (1566-1609) / Yves Junot -- Local categories of residence redefined : the former imperial city of Strasbourg and the politics of the French crown (1681-1789) / Hanna Sonkajärvi -- Instruments of regulation: policies and policing -- Who is not welcome? : reception and rejection of migrants in early modern Italian cities / Eleonora Canepari -- Immigration policy in eighteenth-century Trieste / Aleksej Kalc -- Urban police and the regulation of migration in eighteenth-century France / Vincent Milliot -- Crossing the lines : begging and poor relief -- Magistrates, beggars, and labourers : migration and regulation in sixteenth-century Ulm / Jason P. Coy -- Regulating urban migration and relief entitlements in eighteenth-century Brabant / Anne Winter -- Rough lives : autobiography and migration in eighteenth-century England / Tim Hitchcock -- Comparisons and conclusions -- Cities, states and migration control in western Europe : comparing then and now / Leo Lucassen